Growth of ultra small self-assembled InGaN nanotips - Ji, L.W.; Su, Y.K.; Chang, S.J.; Fang, T.H.; Wen, T.C.; Hung, S.C. (Journal of crystal growth, 2004)
Vertical self-organized nanotips were grown on InGaN film via metal-organic chemical vapor deposition (MOCVD) and thermal annealing. It was found that typical height of these nanotips is 20nm with an average width of 1nm. It was also found that the local density of the vertically grown self-assembled InGaN nanotips could reach 1.6×1013cm−2. Furthermore, it was found that height and width of the nanotips both distributed uniformly. The possible formation mechanism of self-assembled nanotips has been also discussed in this work. Such a small size of vertical nanotips could show strong quantum localization effects and have potential applications in field emission devices, near-field microscopy, and blue photonics.